STRUCTURAL AND BIOMECHANICAL ANALYSIS OF DISCUS THROW - Grujo Bjeković; Izudin Tanović; Ratko Pavlović; Gorjan Vuksanović; Đorđe Arnaut (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Discus throw is track and field event with acyclic type of movement. It is performed with specific rhythm. Athlete tries to direct maximal speed from all of the body segments towards the discus in order to achieve the maximum result. Beside initial velocity, discus position at the time of the throw and its rotation around its axis largely influence on throw length. During its flight discus is exposed to aerodynamic forces, which can extend or reduce its trajectory. The best results are accomplished by circular movement of the body, by which discus is thrown 8 to 12 meters. This part of the body movement which influences on the discus is performed in the interval of 0.14 to 0.16 seconds. It is common for all throwing events that throwing technique is divided into four phases with different sub phases.